PERAN BANK SYARIAH DALAM MENGURANGI KEMISKINAN - Hamid, Abdul; Aris, Aris (DIKTUM: Jurnal Syariah dan Hukum, 2017)
Abstract: This paper will see the Islamic Bank as an Islamic financial institution in order to participate in improving the welfare of all communities. Islamic banks have different purposes than conventional banks, Islamic banks as syariah-based banks and morals have a goal not only to achieve profit but also have social and spiritual goals (maqhasid shariah). Therefore the preparation of Sharia Bank business plan must be based on sustainable business principles and based on worldly balance with the creation of prosperity (maslahat) towards the achievement of eternal victory (falah).